THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE DEVELOPMENT OF SCIENTIFIC RESEARCH COMPETENCES OF MASTER'S STUDENTS IN A DIGITAL EDUCATIONAL ENVIRONMENT - Usmanova Umida Aybekovna (Bright Mind Publishing, 2025)
This article discusses the impact of artificial intelligence on the development of scientific research competencies of master's students. It also emphasizes the need for master's students to be aware of scientific approaches, concepts, theories, and the latest information in their discipline during their studies at a higher educational institution and their subsequent professional development.
Keywords: innovation, science, scientific and pedagogical activity, research, scientific research, discovery, self-awareness, scientific conferences, intellectual-developmental.